Finite element analysis on badminton racket design parameters. ([2016]) - Nasruddin, Fakhrizal Azmy; Muhamad Noor Harun; Ardiyansyah Syahrom; Mohammed Rafiq Abdul Kadir; Omar, Abdul Hafidz; Öchsner, Andreas
No abstract available